Estudo da criatividade no contexto do trabalho à luz da Psicologia Histórico-Cultural - Coelho, Talitha Priscila Cabral (2012)
This dissertation is the result of a bibliographical research carried out in the Postgraduate Program in Psychology at the State University of Maringá (2010-2011), and is joined to the study area of Constitution of the Subject and Historicity as well as the project entitled Psicologia histórico-cultural e defectologia: estudo das contribuições/implicações teóricometodológicas soviéticas para a apropriação da linguagem verbal por alunos com deficiências e para a constituição das suas subjetividades (UEM, 2007-2013). It concerns the creative activity in the work setting. It is justified by the researcher's experience in this field as a psychologist and as a teacher, and especially, by the evidence of lack of research and writings about its subject matter. It aims at investigating, on the groundwork of historicalcultural psychology, the creative manifestation at the adult age and its relationship with the process of human education for the productive life in order to contribute to the education of psychologists in the education and work fields. It results from a bibliographical-conceptual research based on the Marxist theoretical framework and historical-cultural psychology foregrounding. Regarding its proceedings, a mapping of how well the creativity theme in work psychology has been approached as well as the adopted theoretical perspectives was conducted. Current hegemonic formulations about creativity at work were examined in an effort to identify how the concept of creativity is being introduced and which theoretical approach supports researches on this theme. A profound study of L. S. Vygotsky's elaborations and other scholars' from historical-cultural psychology, writings concerning the material conditions of URSS which constituted such psychology, Taylor's, Ford's and Ohno's writings on the organization of workers in the capitalist productive process, his or her psychological development subjected to the efficiency of the productive process and their implications for the creative capability was made. The outcomes of this study show the need for conceptualizing and explaining the development of the creative processes, taking into consideration the great presence of writings on this theme that conceptualize creativity inconsistently, multidimentionally; the relevance for the work psychologist to get to know about the current setting that deals with a capital and work relationship in face of a productive reestablishment, its consequences to the working class and his or her own profession. In conclusion, it acknowledged that despite Vygotsky's work dates from the early twentieth century, his statements are present for asserting a conception of subject and his or her psyche as a synthesis of multiple determinations of the real, historically and wholly understood. It is important to remark history as a theoretical and methodological instrument for the advancement in psychological science studies so as neither individualizing nor naturalizing man, his or her psyche, his or her lack of creativity.